A more global approach to musculoskeletal pain: Expressive writing as an effective adjunct to physiotherapy - Pepe, Luisa; Milani, Roberta; Di Trani, Michela; Di Folco, Gianluca; Lanna, Vittorio; Solano, Luigi (Psychology, health & medicine, 2014)
The aim of this study was to investigate the effects of written emotional disclosure as an adjunct to physiotherapy. Forty outpatients with musculoskeletal pain were treated with Mézières physiotherapy for 10 sessions. Half of the subjects also wrote about difficult life experiences immediately after four of these sessions. Data analysis showed that although both the writing and non-writing groups displayed lower pain scores after physiotherapy, the difference was stronger in the writing group. Pain scores continued to decrease six months after physiotherapy in the writing group alone. The postural evaluation revealed a greater improvement in the writing group than in the non-writing group, while the TAS-20 and SCL-90 scores decreased in the writing group alone. These results indicate that written emotional disclosure is an effective adjunct to physiotherapy insofar as it promotes further health improvements at both the physical and psychological levels.